Mechanochemical synthesis of nanostructured nickel and nickel-zinc ferrites and investigation of their structural and magnetic properties - Hajalilou, Abdollah (2015)
For several past decades, studies of the relationship between morphological and magnetic properties of ferrites have been focusing only on the final sintering temperature, largely neglecting the parallel evolutions of morphological and magnetic properties and their relationship at various sintering temperatures. Hence, here, a new method of high energy ball milling was employed to attempt synthesizing two technologically applicable soft magnetic materials, namely Ni-ferrite and Ni1-xZnxFe2O4 ferrite, for Zn contents x = 0.36 and 0.64, and to elucidate the relationship between morphological, magnetic and electrical properties at different sintering temperatures. Subsequently, common oxides of 0.4CaO + 0.8SiO2 were added to the Ni0.36Zn0.64Fe2O4 ferrite to observe the resulting property changes. In the first work section, NiFe2O4 nanoparticles were synthesized by a mechanochemical reaction of NiO and Fe2O3 powders in a high energy planetary ball mill. The X-ray diffraction (XRD) results indicate that the NiO/Fe2O3 particles reacted in a solid-state reaction mode, producing nickel ferrite particles ranging from 5 to 18 nm in size after 18 h of milling. The effects of milling time, rotation speed, and ball to powder weight ratio were investigated and the contribution of each parameter was evaluated by using the Taguchi robust design method. It was found that rotational speed had the most effect on the crystallite size. By sintering 30 h-activated compacted samples from 900 to 1300 ºC, with 100 ºC increments, a dependence of magnetic and electrical properties on sintering temperature was found, thus improving magnetic properties i.e. saturation magnetization and reduction of electrical resistivity with increase in the sintering temperature. In the second work section, high-energy ball milling with a subsequent heat treatment method was carried out to synthesize nanocrystalline Ni1-xZnxFe2O4 ferrite with x = 0.36 and 0.64 from a powder mixture of pure metal Zn, Fe2O3 and NiO. The effect of milling atmospheres (argon, air and oxygen), milling time and sintering temperature was investigated. The XRD results indicated that a single phase of Ni-Zn ferrite was not produced after 30 h milling in the all three atmospheres of air, argon and oxygen for both compositions except for the milled samples in argon for Zn content at x = 0.64. However, single phase Ni-Zn ferrite was later produced after sintering the other samples of 30 h-milled powders at 500 ºC for 2 h. The 30 h-milled powders in different atmospheres were pressed into pellet/toroid form and subjected to sintering in air in the same conditions from 400 to 900 ºC for 2 h. Increasing sintering temperature improved the magnetic properties but degraded the DC electrical resistivity. In terms of milling atmosphere, however, the milled-sintered samples in argon presented the lowest crystallite size, as compared to the two other atmospheres, they exhibited the highest Ms. By increasing the Zn content the lattice parameter and density of the samples increased while the saturation magnetization, crystallite size, porosity and resistivity decreased. Furthermore, by increasing milling time from 6 h to 18 h a synthesis temperature of Ni0.36Zn0.64Fe2O4 remarkably was reduced from 500 to 300 ºC, respectively. The Ni-Zn ferrite formation mechanism was detected to be in three stages: oxidation of zinc, diffusion of ZnO in Fe2O3 thus the forming ZnFe2O4, and diffusion of NiO in ZnFe2O4 thus forming Ni-Zn ferrite. Furthermore, Fourier transform infrared spectroscopy (FT-IR) results suggested the presence two absorption bands for octahedral and tetrahedral sites in the range of 350-700 cm-1. Finally, the common oxides (X = 0.4CaO + 0.8SiO2) were added in different moles (X = 0, 0.02, 0.06, 0.12, 0.24 and 0.48) to Fe2O3, Zn, and NiO. The mixed powders were mechanically alloyed for 12 h and then were sintered at 1200 ºC for different times. It was found that there was a dependence of spinel ferrite properties i.e. microstructure, electrical and magnetic properties with both X contents and sintering time. For example, magnetic parameters such as saturation magnetization (Ms) and induction magnetization (Bs) degraded while resistivity improved by increasing the X content.